Widening Participation in University Learning - Rissman, Barbara; Carrington, Suzanne; Bland, Derek (Journal of University Teaching and Learning Practice, 2013)
This paper reports how one Australian university and the Queensland Department of Education and Training (DET) are working together to increase the number of school students from low socio-economic backgrounds enrolling in undergraduate university degrees. This innovative program involves university lecturers and school teachers working together in the delivery and assessment of four Bachelor of Education units (or subjects) to a cohort of Year eleven and twelve students at a secondary school. Focus group interviews collected data from 26 students, 7 parents, 4 school and 3 university staff to assess the effectiveness of the program. All stakeholders viewed the program as a highly valuable opportunity to experience university learning with 31 high school graduating students being made offers to enter full-time university in the 2010 and 2011. This positive result has particular significance in the current drive in Australia and elsewhere to increase the participation in higher education of young people from under-represented groups.